2007
DOI: 10.1002/ardp.200600118
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Some Novel Substituted Purine Derivatives As Potential Anticancer, Anti‐HIV‐1 and Antimicrobial Agents

Abstract: In search of novel purine antimetabolites, a series of 8-substituted methylxanthine derivatives was prepared in order to explore their in vitro anticancer, anti-HIV-1 and antimicrobial activities. The target compounds include: 8-[(3-substituted-4-oxo-thiazolidin-2-ylidene)hydrazino]-1,3-dimethyl (or 1,3,7-trimethyl)-3,7-dihydropurine-2,6-diones 5a-e, 8-[(3,4-disubstituted 2,3-dihydrothiazol-2-ylidene)hydrazino]-1,3,7-trimethyl-3,7-dihydropurine-2,6-diones 6a-d and 8-(5-amino-3-arylpyrazol-1-yl)-1,3-dimethyl- (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The cationic l- α,γ-diaminobutyric acid residues of the polymyxin molecule produce an electrostatic attraction to the negatively charged lipid A phosphate groups, displacing the divalent cations (Mg 2+ and Ca 2+ ) [8]. The displacement leads to the disorganization of the LPS leaflet, enabling the insertion of the hydrophobic tail and the hydrophobic side chains of amino acids 6 and 7 of the polymyxin molecule into the OM [24]. Polymyxin resistance in K. pneumoniae primarily involves the multi-tier upregulation of capsular polysaccharide expression, and the systems required for the modification of lipid A with 4-amino-4-deoxy- l- arabinose and palmitoyl addition [20,23,25,26,27,28,29,30,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…The cationic l- α,γ-diaminobutyric acid residues of the polymyxin molecule produce an electrostatic attraction to the negatively charged lipid A phosphate groups, displacing the divalent cations (Mg 2+ and Ca 2+ ) [8]. The displacement leads to the disorganization of the LPS leaflet, enabling the insertion of the hydrophobic tail and the hydrophobic side chains of amino acids 6 and 7 of the polymyxin molecule into the OM [24]. Polymyxin resistance in K. pneumoniae primarily involves the multi-tier upregulation of capsular polysaccharide expression, and the systems required for the modification of lipid A with 4-amino-4-deoxy- l- arabinose and palmitoyl addition [20,23,25,26,27,28,29,30,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…However, some have been reported only during the last few years. In brief, the biological activities of most of the purine derivatives are briefly described 9 as potential anticancer, anti-HIV-1, antimicrobial agents and in some cases, syntheses are formulated.…”
Section: Introductionmentioning
confidence: 99%
“…Purines are valuable compounds with special impact in the area of medicinal chemistry, with a number of derivatives presenting antifungal, 1,2 antibacterial, 1,2 antimycobacterial, 2 anticancer, 3 and antiviral 4 activity. The synthesis of substituted purines has been addressed in several review articles, but only a few 8-aryl-6-cyanopurines have been reported from 8-bromo, 5 8-methyl 6 or 8-carbonyl 7 substitution on the purine scaffold.…”
mentioning
confidence: 99%